A Model Framework of Entrepreneurial Team Formation Embedded in Venture Development Stages : An Agenda for Future Research - Gethe, Rajashree; Pandey, Ashish (Prabandhan: Indian Journal of Management, 2026)
Purpose : The purpose of the study was to investigate how entrepreneurs form the team, collaborate, and exit during the venture inception, venture development, and venture decline phases. Design/Methodology/Approach : The present research employed a qualitative methodology, specifically a Systematic Literature Review, in the context of entrepreneurship. Findings : The study found that the “entrepreneurial team’s life cycle” was embedded in every phase of the venture life cycle, i.e., venture inception, venture development, and venture decline, where entrepreneurial team members experienced different events in each phase of the venture. Practical Implications : Occurrences of conflicts among entrepreneurial team members would enable founding members to adopt conflict resolution strategies for resolving conflicts with ease, leaving less impact on business performance during the team development and venture development stages. Originality : The study identified unexplored research areas in entrepreneurship, including entrepreneurial team task allocation and conflict management, opportunity evaluation and recognition, team member exit and its impact on venture development, and team behavior during the venture decline phase.